Antibacterial, anti‐inflammatory, analgesic, and hemostatic activities of Acanthopanax trifoliatus (L.) merr. Issue 4 (28th February 2021) - Chen, Zefeng; Cheng, Shupeng; Lin, Huiqiong; Wu, Wenjing; Liang, Liyi; Chen, Xicai; Zheng, Xi; He, Yan; Zhang, Kun
Abstract: Acanthopanax trifoliatus (L.) Merr (AT) is a medicinal and edible plant with high nutritional value. The biological activity of A. trifoliatus (L.) Merr and its basis for injury treatment are explored in this paper. AT was ethanol‐extracted then refined separately with petroleum ether, chloroform, ethyl acetate, and n‐butanol. Active ingredients were analyzed, and anti‐bacterial, anti‐inflammatory, analgesic, and hemostatic effects were explored. Petroleum ether layer (PEL) extract produced the strongest antibacterial effect. Ethyl acetate layer (EAL) extract had the highest active substance content, with strong hemostatic and analgesic activities. Chloroform layer (CL) extract had the strongest anti‐inflammatory effect and significantly reduced IL‐1β protein expression. Active ingredients were analyzed using HPLC and UPLC‐MS to determine saponin, polyphenol, flavonoid, and characteristic ingredient contents. EAL extract had the highest polyphenol and flavonoid levels, including rutin, chlorogenic acid, isochlorogenic acid A, and isochlorogenic acid C, which may contribute to its nutritional activities. The study provides a reliable theoretical and practical basis for the applications of AT nutraceutical products. Abstract : Organic solvent layer extracts of Acanthopanax trifoliatus (L.) Merr (AT) have various biological activities. Extracts produced strong antibacterial, anti‐inflammatory, analgesic, hemostatic activities and reduced IL‐1β protein expression. These results provide a reliable theoretical and practical basis for the research and development of a topical application of AT products.